Effects of salinity stress on the seed germination and seedling characters of carrots (Daucus carota L.) - Rashid, Md. Harun Ar; Tuz-Zahura , Mst. Fatema; Suchi, Kaniz Fatema; Anjum, Nafisa; Tasmim, Mst. Tamanna; Simon, Philipp (Fundamental and Applied Agriculture, 2024)
Carrot is an important root vegetable and salinity has strong effect on its seed germination and seedling characters. An experiment was conducted at the Postgraduate Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from July to August, 2023 to study the effect of salinity stress on the seed germination and seedling characters of four carrot varieties. The two-factor experiment consisted of four carrot varieties viz. Orange king, Orange star, Sangal and Red lady, and five salinity levels viz. control (tap water), 25 mM, 50 mM, 75 mM and 100 mM NaCl. The experiment was laid out in completely randomized design with three replications. Results revealed that salinity and carrot varieties significantly influenced all the parameters studied. The highest seed germination (44.44%) was obtained from Orange king while the lowest (32.89%) was obtained from Red lady. The highest seed germination (41.11%) was obtained from 100 mM NaCl solution and the lowest (34.44%) was found from 75 mM NaCl. Among the treatment combinations, the highest seed germination (60.00%) was obtained from Orange king along with 50 mM NaCl. The maximum radicle (15.46 mm) and plumule length (12.36 mm), leaf size (5.50 mm), number of leaves (2.73) and seedling height (27.82 mm) was obtained from Orange king. Maximum plumule length (13.27 mm), leaf size (5.98 mm) and seedling height (23.27mm) was obtained from control treatment and maximum number of leaves (2.08) from 25 mM NaCl solution. Among the treatment combinations, highest radicle length (18.27 mm), plumule length (17.40 mm), leaf size (7.60 mm), seedling height (35.67 mm) was obtained from Orange king along with 25 mM NaCl solution. Therefore, Orange king along with 50 mM NaCl solution and 25 mM NaCl solution was found to be better in respect of seed germination and seedling characters of carrots compared to other treatments respectively.